2007
DOI: 10.1523/jneurosci.2252-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Temporal Correspondence Modulates Human Multisensory Superior Temporal Sulcus Plus Primary Sensory Cortices

Abstract: The brain should integrate related but not unrelated information from different senses. Temporal patterning of inputs to different modalities may provide critical information about whether those inputs are related or not. We studied effects of temporal correspondence between auditory and visual streams on human brain activity with functional magnetic resonance imaging (fMRI). Streams of visual flashes with irregularly jittered, arrhythmic timing could appear on right or left, with or without a stream of audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
240
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(283 citation statements)
references
References 67 publications
41
240
1
1
Order By: Relevance
“…Previous studies have shown that posterior STS responds more to multisensory auditory-visual stimuli than to unisensory auditory or visual stimuli (Beauchamp et al, 2004b;Calvert, 2001;Hein et al, 2007;Noesselt et al, 2007;Raij et al, 2000;Van Atteveldt et al, 2004). Consistent with these results, we observed a larger response for multisensory auditory-tactile stimuli than unisensory auditory or tactile stimulation.…”
Section: Multisensory Integration In Stsmssupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that posterior STS responds more to multisensory auditory-visual stimuli than to unisensory auditory or visual stimuli (Beauchamp et al, 2004b;Calvert, 2001;Hein et al, 2007;Noesselt et al, 2007;Raij et al, 2000;Van Atteveldt et al, 2004). Consistent with these results, we observed a larger response for multisensory auditory-tactile stimuli than unisensory auditory or tactile stimulation.…”
Section: Multisensory Integration In Stsmssupporting
confidence: 91%
“…In the banks of human posterior STS, neuroimaging studies have reported multisensory responses to auditory and visual stimulation (Beauchamp et al, 2004b;Calvert, 2001;Noesselt et al, 2007;Van Atteveldt et al, 2004;Wright et al, 2003). This region has been termed STSms, the STS multisensory region (Beauchamp et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…At the neural level, asynchronous relative to synchronous conditions increased activation in a distributed neural system encompassing bilateral STS/MTG, occipital and fusiform gyri, and premotor and cerebellar cortices (6,7). This asynchrony system was largely shared by speech and music, with no asynchrony effects that were specific to speech or music.…”
Section: Resultsmentioning
confidence: 90%
“…Although speech elicited comparable asynchrony effects in musicians and nonmusicians in posterior STS/MTG bilaterally and left cerebellum, music evoked increased asynchrony effects for musicians relative to nonmusicians in left premotor cortex, left cerebellum, and right posterior STS/MTG. Hence, audiovisual asynchrony is detected automatically not only along the sensory processing hierarchies and classical audiovisual integration areas such as STS (7,20,21) but also in a premotor-cerebellar circuitry. Importantly, the asynchrony effects within the premotor-cerebellar circuitry depended on the availability of prior sensory-motor experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation